LiMA: A study protocol for a randomised, double-blind, placebo controlled trial of lisdexamfetamine for the treatment of methamphetamine dependence - Ezard, N.; Dunlop, A.; Hall, M.; Ali, R.; McKetin, Rebecca; Bruno, R.; Phung, N.; Carr, A.; White, J.; Clifford, B.; Liu, Z.; Shanahan, M.; et al. (BM J Group, 2018)
© Author(s) (or their employer(s)) 2018. Re-use permitted under CC BY-NC. No commercial re-use. See rights and permissions. Published by BMJ. Introduction Methamphetamine dependence is a growing public health concern. There is currently no pharmacotherapy approved for methamphetamine dependence. Lisdexamfetamine (LDX) dimesylate, used in the treatment of attention-deficit hyperactivity disorder and binge eating disorder, has potential as an agonist therapy for methamphetamine dependence, and possible benefits of reduced risk of aberrant use due to its novel formulation. Methods and analysis A double-blind randomised controlled trial will be used to evaluate the efficacy of LDX in reducing methamphetamine use. The target sample is 180 participants with methamphetamine dependence of =2 years, using =14 days out of the previous 28, who have previously attempted but not responded to treatment for methamphetamine use. Participants will be randomly assigned to receive either a 15-week intervention consisting of induction (1 week of 150 mg LDX or placebo), maintenance (12 weeks of 250 mg LDX or placebo) and reduction (1 week of 150 mg LDX or placebo and 1 week of 50 mg LDX or placebo). All participants will be given access to four sessions of cognitive-behavioural therapy as treatment as usual and receive a 4-week follow-up appointment. The primary outcomes are efficacy (change from baseline in days of methamphetamine use by self-report for the last 28 days at week 13 and urinalyses confirmation of methamphetamine use) and safety (treatment-related adverse events). Secondary outcomes are total number of days of self-report methamphetamine use over the 12-week active treatment, longest period of abstinence during treatment period, percentage of achieving =21 days abstinence, craving, withdrawal, dependence, retention, bloodborne virus transmission risk behaviour, criminal behaviour, as well measures of abuse liability, physical and mental health, other substance use, cognitive performance, psychosocial functioning, treatment retention and satisfaction. Additionally, the study will assess the cost-effectiveness of LDX relative to the placebo control. Ethics and dissemination The study has been approved by the Human Research Ethics Committee of St. Vincent's Hospital, Sydney, Australia (HREC/16/SVH/222). Contact the corresponding author for the full trial protocol. Trial registration number ACTRN12617000657325; Pre-results.